A RHCP Microstrip Antenna with Ultrawide Beamwidth for UHF Band Application - Yuan-zhu Liu; Shao-qiu Xiao; Bing-zhong Wang (International Journal of Antennas and Propagation)
A novel right-hand circularly polarized (RHCP) UHF microstrip antenna with 3 dB beamwidth of more than 150° is presented in this paper. The 3 dB RHCP beamwidth can be broadened by utilizing a combined ground structure with a hollow truncated cone ground plane and a metallic rectangular plate. Optimizing the half-angle θc of cone and the cone height hcone, a 3 dB RHCP beamwidth of more than 200° can be acquired, which is about 120° greater than its corresponding regular RHCP microstrip antenna. There is a good agreement between the measured results and simulated results for the proposed antenna operating in UHF band.